Evaluation of the Physical Education Teacher Performance Assessment Program in Cimahi City - Pandu Futuhatul Firdaus; Akhmad Sobarna; Hendya Alif Junanda (STKIP Pasundan Press, 2026)
This study aims to evaluate the effectiveness of the Teacher Performance Assessment (PKG) program in enhancing the professional competence of Physical Education, Sports, and Health (PJOK) teachers in Cimahi City. Using a mixed-method approach with the CIPP model (Context, Input, Process, Product), the study involved 30 PJOK teachers selected through purposive sampling. Data were collected using questionnaires, interviews, observations, and documentation, and analyzed through data reduction, presentation, and conclusion. The findings reveal that the PKG program was not optimally implemented across all four dimensions. In the context dimension, the program's goals did not fully align with teacher needs. Input aspects, including training and infrastructure, were insufficient. The process dimension showed inadequate socialization and implementation. In the product dimension, the impact on teacher competence was still limited. It is concluded that the PKG program requires continuous training, structured evaluation, and more effective communication to achieve its intended goals.